STRATEGI PENGEMBANGAN UMKM TEMPE MENGGUNAKAN METODE ANALISIS SWOT - Hayan, Maulana Thoriqul; Hamjah, Siti Amalia; Andriani, Pety Rasti; Budiharjo, Budiharjo (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the national economy, especially in developing countries like Indonesia. MSMEs often face various challenges that hinder the development of their businesses. Some of the main challenges faced by MSMEs include limited access to capital, lack of managerial skills, limited market access, low levels of technology adoption, and competitive pressures from local and global products. MSME Tempe Ibu Marsiyah has a very open potential to develop further, therefore a planned and sustainable development strategy is needed to increase the competitiveness and sustainability of MSMEs. One approach that can be used is the SWOT Analysis method (Strengths, Weaknesses, Opportunities, Threats). The SWOT analysis method is a methodology for finding the relationship between the company's external opportunities and threats, with the company's internal strengths and weaknesses (Gunawan, 2020). The function of SWOT analysis and competitive strategy is to analyze the weaknesses, strengths and competitive advantages of a business/company, which is carried out through an analysis of internal conditions, and is carried out through an analysis of the company's external conditions regarding the opportunities and threats faced by the company. SWOT Analysis Covers 4 Pillars of Internal & External Analysis, namely: Based on the results of the SWOT graph, UMKM Tempe Ibu Marsiyah is in quadrant 1, which is a Growth situation. This position shows that UMKM has internal strengths that support it to optimally utilize external opportunities. The recommended strategy for this condition is an Aggressive Strategy, which focuses on business development, expanding the market, increasing production, or strengthening competitive advantages to drive growth. In other words, UMKM Tempe Ibu Marsiyah is in good condition to take proactive steps to expand and strengthen the business. Based on the Results of the SWOT Analysis, the Application of SWOT to UMKM Tempe Ibu Marsiyah is the calculation results in the IFAS and EFAS tables with a comparison between strengths and weaknesses, the IFAS calculation shows that Strength is greater than Weakness. Meanwhile, the EFAS calculation shows that Opportunity is greater than Threat, thus Rumah Sayur UMKM must choose and use an aggressive or developing strategy, which includes conditions of strength and opportunity to be in a good position or SO Strategy where readiness for technology is also the most important factor in driving UMKM.